Heat stress affects milk yield, milk quality, and gene expression profiles in mammary cells of Girolando cows - Mendonca, L. C. [UNESP]; Carvalho, W. A.; Campos, M. M.; Souza, G. N.; de Oliveira, S. A.; Meringhe, G. K.F.; Negrao, J. A. (American Dairy Science Association, 2025)
Heat stress during lactation affects the physiological responses, hormonal release, health, and productivity of dairy cows. However, the adverse effects of heat stress on milk synthesis, immune response, and cellular apoptosis in mammary cells remains unknown in Bos indicus cows. This study aimed to understand the relationship between milk yield, milk quality, and the expression of genes related to milk synthesis, cell apoptosis, and immune response in mammary cells of Girolando cows. A total of 24 Girolando cows (3/4 Holstein and 1/4 Gir) were subjected to control (CT; with a temperature-humidity index ranging from 60 to 74, n = 12) or heat stress treatments (HS; with a temperature-humidity index ranging from 60 to 85, n = 12), from 111 to 120 d of lactation. Heat stress significantly increased the expression of heat shock proteins (HSPD1 and HSPD90AA1), insulin receptors (INSR), and prolactin receptor (PRLRsf) genes, and decreased the expression of glucocorticoid receptor (NR3C1) gene in mammary cells of the HS cows when compared with the CT cows. The HS cows exhibited significantly higher vaginal temperatures and cortisol release compared with the CT cows. Moreover, the HS cows had significantly lower DMI and milk yield than CT cows. Although, HS cows showed higher percentage of lymphocytes in milk when compared with that from CT cows. We found no effect of heat stress on other leukocyte counts, somatic cell counts, bacterial counts in milk, or milk composition. Finally, this study demonstrated that Girolando cows are susceptible to heat stress, which decreases milk yield and affects the expression of genes linked to milk synthesis in the mammary cells.
Keywords: gene expression; Girolando; heat stress; mammary cells; milk yield